Binary breath figures for straightforward and controllable self-assembly of microspherical caps. Issue 19 (3rd May 2016) - Gong, Jianliang; Xu, Bingang; Tao, Xiaoming; Li, Lei
Abstract : A binary breath figure approach of using water and methanol has been developed for controllable self-assembly of microspherical caps. Abstract : The intense interest surrounding asymmetrical microparticles originates from their unique anisotropic properties and promising applications. In this work, direct self-assembly of polymeric microspherical caps without the assistance of any additives has been achieved by using low-surface-tension methanol (MeOH) and high-surface-tension water as binary breath figures (BFs). With the evaporation of polystyrene (PS) solution containing low-boiling-point solvent in the binary vapors, the formed MeOH BFs could quickly diffuse into solution, while water BFs tended to remain at the solution surface. This led to the formation of a gradient nonsolvent layer at the vapor/solution interface, which induced the formation of nuclei and guided further asymmetrical growth of polymer particles. After the spontaneous removal of MeOH, water and residual solvent by evaporation, polymeric microspherical caps were left on the substrate. Through controlling the proportion of water introduced by adjusting the ratios of MeOH and water, polymeric microspherical caps with a range of controllable shapes (divided at different positions of a sphere) were successfully obtained. The formation mechanism was explained based on the difference of vapor pressure, surface tension and miscibility between the employed solvents and nonsolvents. A solvent possessing a high vapor pressure, low surface tension and good miscibility with MeOH contributed to the formation of microspherical caps. This flexible, green and straightforward technique is a nondestructive strategy, and avoids complicated work on design, preparation and removal of hard templates and additives.